Metabolic syndrome in people with a psychotic illness: is cannabis protective?. Issue 8 (11th March 2016) - Waterreus, A.; Di Prinzio, P.; Watts, G. F.; Castle, D.; Galletly, C.; Morgan, V. A.
Abstract : Background: Rates of the metabolic syndrome in people with psychotic illness are high. Emerging evidence suggests that cannabis use may have a positive impact on cardiometabolic risk factors in the general population, but little is known about its impact for people with psychotic illness. Our aim was to investigate whether the rate of the metabolic syndrome in people with psychotic illness was associated with frequency of cannabis use. Method: The 2010 Australian psychosis survey used a two-phase design to randomly select a nationally representative sample of 1825 adults with psychotic illness for interview and physical assessment. This study is based on 1813 participants who provided data on cannabis use. Multiple logistic regression was used to model the influence of frequency of cannabis use on the metabolic syndrome, adjusting for potential covariates including antipsychotic medication use, smoking, alcohol use and cognitive function. Results: One-third (33.0%) of participants had used cannabis in the past year. The proportion of non-users, occasional users and frequent users with the metabolic syndrome was 63.0, 51.7 and 43.5%, respectively ( p < 0.001). In unadjusted analyses, both occasional use and frequent cannabis use were associated with significantly lower odds of the metabolic syndrome. In the adjusted analyses, the association between the metabolic syndrome and frequent cannabis use remained significant [odds ratio = 0.56, 95% confidence interval (CI) 0.39–0.80], but not the association with occasional use (odds ratio = 0.75, 95% CI 0.49–1.13). Conclusions: While cannabis use may be detrimental for mental health, these data suggest that it may also have a cardiometabolic protective effect. Further investigation is required to understand the mechanism underlying this paradoxical finding.